Tetanus is a difficult diagnosis in children - E. M. Simovanyan; E. L. Goncharova; V. B. Denisenko (LLC "Diagnostics and Vaccines", 2019)
The sporadic incidence of tetanus, the identity of symptoms with the clinical picture of a number of common neuroinfections, the high frequency of various background pathologies create difficulties in disease diagnosing in children. On the case history example of a 3 years 9 months old child with two diseases (tetanus, enterovirus infection) that developed against the background of the active form of herpesvirus infection, an algorithm of diagnostic and therapeutic measures is presented.A differential diagnosis was made between the generalized form of tetanus and meningoencephalitis of enteroviral etiology. Lack of vaccination, living in rural areas, violation of the integrity of the skin and soil contamination testified in favor of tetanus. The clinical symptoms of tetanus were revealed: a triad of symptoms (trismus, «sardonic smile», dysphagia), tetanic cramps against a background of clear consciousness, muscle hypertonicity in the interictal period. The patient received complex treatment; 100 thousand IU of anti-tetanus serum and tetanus anatoxin were introduced. Discharged on the 23rd day of illness with recovery.